Meningitis in a Canadian Adult due to High Level Penicillin-Resistant, Cefotaxime-Intermediate Streptococcus pneumoniae. (1996) - Tremblay, Cécile; Bourgault, Anne-Marie; St-Antoine, Pierre
Abstract : Invasive penicillin-resistant pneumococcal (PRSP) infections are increasing worldwide. In Canada, the incidence of penicillin resistance among Streptococcus pneumoniae isolates is estimated at greater than 6%. In Quebec, only one case of PRSP meningitis has been reported and involved an infant. An adult patient is described who presented with meningitis caused by high level penicillin-resistant, cefotaxime-intermediate S pneumoniae .